Effect of the feed supplement Bio-Mos, a mannan-oligosaccharide, on the performance of broiler chickens - SPAIS (Α.Β. ΣΠΑΗΣ) A. B.; GIANNENAS (Ι.Α. ΓΙΑΝΝΕΝΑΣ) I. A.; FLOROU-PANERI (Π. ΦΛΩΡΟΥ-ΠΑΝΕΡΗ) P.; CHRISTAKI (Ε. ΧΡΗΣΤΑΚΗ) E.; BOTSOGLOU (Ν.Α. ΜΠΟΤΣΟΓΛΟΥ) N. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The effect of the mannan-oligosaccharide Bio-Mos on broiler chicken performance, after its incorporation in the starter diet was evaluated. A total of 53,040 one day-old Cobb chicks, randomly divided into two groups with four replicates each, were used in a feeding trial that lasted 40 days. One of the groups (Control group) was fed on a basal commercial starter diet, while the other (Bio-Mos group) was given up to day 10 of age the same diet supplemented with the mannan-oligosaccharide Bio-Mos at the level of 1.5 g/kg of feed. From day 11 of age and thereafter, Bio-Mos administration was discontinued and both groups were given the same basal commercial grower and finisher diets. Results showed that chickens in the Bio-Mos fed group exhibited a significant (P<0.05) improvement in body weight compared to control at day 10 (295 vs 254 g) and day 40 (2108 vs 2017 g) of age. Feed intake per bird from day-old to day 40 of age showed a significant (P<0.05) increase in the Bio-Mos group compared to control (3647 vs 3612 g), whereas feed conversion ratios also demonstrated a significant (P<0.05) improvement for the Bio-Mos group (1.73 vs 1.79). Mortality rate was lower in the Bio-Mos group compared to control (2.5 vs 2.9%), however, the difference was not statistically (P>0.05) significant.